"NURSING CARE MANAGEMENT OF MEDICAL-SURGICAL NURSING FOR MRS. E WITH ISCHEMIC STROKE IN ROOM RA1 AT H. ADAM MALIK MEDAN NORTH SUMATRA PROVINCE, YEAR 2025." - Peni Epelina Nainggolan; Sri Mulati Nendah Agreta; Ade Rachmat Yudiyanto; Cecilia Cathrine Caroline; Reysa Aura Purba; Nur Aisah; Desi Agustina, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
ABSTRACT Ischemic stroke is the most common type of stroke, occurring due to a blockage in the blood vessels of the brain, which leads to reduced blood flow and oxygen supply to brain tissue. This condition causes rapid brain cell death and may result in neurological deficits such as paralysis, speech disorders, and loss of consciousness. Risk factors for ischemic stroke include hypertension, diabetes mellitus, dyslipidemia, heart disease, smoking habits, and an unhealthy lifestyle. Stroke is the second leading cause of death and a major cause of disability worldwide. According to the World Health Organization (WHO, 2022), stroke accounts for approximately 6 million deaths each year. About 62% of cases occur in individuals under the age of 70, and 16% occur between the ages of 15–49. In Indonesia, the prevalence of stroke is 8.3 per 1,000 population, while in North Sumatra Province, the incidence rate reaches 9.3%. At RSUP H. Adam Malik, the number of ischemic stroke cases continues to rise: 295 cases in 2023, 393 cases in 2024, and 131 cases in the first two months of 2025. In relation to this, the present study aims to obtain data on the problem of ischemic stroke at RSUP H. Adam Malik. Based on these findings, the researcher prese nts a case study of medical-surgical nursing care for Mr. E with ischemic stroke in the RA1 Ward at RSUP H. Adam Malik.